2013
DOI: 10.1002/aur.1328
|View full text |Cite
|
Sign up to set email alerts
|

Do Children With Autism Re‐Enact Object Movements Rather Than Imitate Demonstrator Actions?

Abstract: It has been suggested that autism-specific imitative deficits may be reduced or even spared in object-related activities. However, most previous research has not sufficiently distinguished object movement reenactment (learning about the ways in which object move) from imitation (learning about the topography of demonstrated actions). Twenty children with autism (CWA) and 20 typically developing children (TDC) were presented with puzzle boxes containing prizes. Test objects and experimental conditions were desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Concerning imitation, it has been suggested that the specific imitation deficit of autism could be reduced or even eliminated with the use of activities linked to objects (Vanvuchelen et al, 2013;Custance et al, 2014), especially when no timelines in the use of objects are given. This would favour a higher joint attention, motor imitation and intentional communication with a social partner (Swettenham et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Concerning imitation, it has been suggested that the specific imitation deficit of autism could be reduced or even eliminated with the use of activities linked to objects (Vanvuchelen et al, 2013;Custance et al, 2014), especially when no timelines in the use of objects are given. This would favour a higher joint attention, motor imitation and intentional communication with a social partner (Swettenham et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…In this way, an electrical buzz wire (EBW) was built as an attractive therapeutic tool. Some authors have demonstrated the use of EBW to assess children's facial expression during errors [8], manual dexterity training [9], and attentional and neuropsychiatric deficits [10], but none investigated the accuracy and precision during eye-hand coordination and object control skill assessment in children.…”
Section: Introductionmentioning
confidence: 99%
“…Williams et al (2005) interviewed parents of 10 children with autism (MA = 62.2 months; SD = 19.9) who reported problems relating to the use of an object, such as an interest in some unusual aspect of the object, an unusual way of using the object, or difficulty in generalizing object use. Custance et al (2014) suggested that imitative deficits in children with autism can be reduced by means of object-related activities, especially if there are no time limits on use of the object. Object-related activities promote joint attention, motor imitation, and intentional communication with a social partner (Bruckner and Yoder, 2007), and there is evidence that interventions focused on play involving different objects can promote social and imitative behaviors (Brown and Murray, 2001;Stahmer et al, 2003;Lee et al, 2017).…”
mentioning
confidence: 99%